BARYON ASYMMETRY IN NEUTRINO MASS MODELS WITH AND WITHOUT ðœ½ðŸï¿½ - Francis, Ng. K. (European Scientific Journal, ESJ, 2015)
We investigate the comparative studies of cosmological baryon asymmetry in different neutrino mass models with and without ðœƒ13 by considering the three diagonal form of Dirac neutrino mass matrices: down quark (4,2), up-quark (8,4) and charged lepton (6,2). The predictions of any models with ðœƒ13 are consistent in all the three stages of leptogenesis calculations and the results are better than the predictions of any models without ðœƒ13 which are consistent in a piecemeal manner with the observational data. For the best model NH-IA (6,2) without ðœƒ13, the predicted inflaton mass required to produce the observed baryon asymmetry is found to be ð‘€ðœ™ 3.6 Ã— 1010 GeV corresponding to reheating temperature ð‘‡ð‘… 4.5 Ã— 106 GeV, while for the same model with ðœƒ13: ð‘€ðœ™ 2.24 Ã— 1011 GeV, ð‘‡ð‘… 4.865 Ã— 106 GeV and weak scale gravitino mass ð‘š2/3 100 GeV without causing the gravitino problem. These values apply to the recent discovery of Higgs boson of mass 125 GeV. The relic abundance of gravitino is proportional to the reheating temperature of the thermal bath. One can have the right order of relic dark matter abundance only if the reheating temperature is bounded to below 107GeV. PACS numbers: 12.60.-I, 14.60.Pq, 95.35. +d, 98.80.Cq